Including Funga in Brazilian environmental impact reports - Amaral-Silva, Isadora [UNESP]; Prado Barcelos, Gabriel [UNESP]; Ganiko-Dutra, Matheus; de Lara Weiser, Veridiana [UNESP] (Elsevier, 2025)
In many countries, Environment Impact Assessment fails in addressing biodiversity. The current legal framework in Brazil restricts the recognition of fungi, leading to gaps in environmental assessments and conservation efforts. This perspective article explores the implications of this legal omission and offers proposals for the inclusion of fungi in Environmental Impact Reports (EIRs) and other relevant conservation documents. The article discusses the importance of fungi in ecosystem sustainability and biodiversity, presenting specific inclusion measures such as fostering specialized mycological groups, implementing mitigation strategies like fungarium creation and fungal rescue programs, and enhancing mycological research. Furthermore, it emphasizes the need for robust public policy support and the integration of fungi in national conservation strategies. The article highlights the urgency of training qualified professionals to effectively incorporate fungi into environmental assessments, ultimately advocating for a more comprehensive and inclusive approach to biodiversity conservation in Brazil, contributing to a global debate about biodiversity in Environment Impact Assessment.
Keywords: Biodiversity; Conservation; Environmental impact assessment; Environmental impact studies; Environmental licensing; Fungi; Mycology